Key Factors for The Successful Management of The Al Musabbihin Mosque - Muhammad Ikhsan Harahap; Rahmat Daim Harahap; Aqwa Naser Daulay; Marliyah Marliyah (Journal of Management and Business Innovations, 2019)
The purpose of this study is to elaborate the management of the mosque. Al Musabbihin mosque located in Taman Setia Budi Indah Medan as an example productive mosque. The Mosque runs by IKMT (Tasbih Muslim Family Association) and managed by the mosque prosperity council. The research was studied qualitatively through descriptive approach. The result shows that the management is run professionally, funds are managed by a different door mechanism to implement consumptive and productive activities. Keywords:  Productive,  mosque management,  funds.